Answer:
[tex](x^{2}+ y^{2})^{2} =x^{4}+2x^{2}y^{2}+y^{4}[/tex]
Step-by-step explanation:
(X^2+y^2)^2 polynomial identify. Simplify
i.e
[tex](x^{2}+ y^{2})^{2} = ?[/tex]
Solution:
We have the identity,
[tex](A+B)^{2}=A^{2}+2AB+B^{2}[/tex]
In the Question
[tex]A=x^{2}[/tex]
[tex]B=y^{2}[/tex]
Substituting in the identity we get
[tex](x^{2}+ y^{2})^{2} =(x^{2})^{2}+2(x^{2})(y^{2})+(y^{2})^{2}[/tex]
Also we have
[tex](x^{a})^{b} =x^{a\times b}[/tex]
[tex](x^{2}+ y^{2})^{2} =x^{4}+2x^{2}y^{2}+y^{4}[/tex] Which is the required